PENGARUH VARIASI JENIS PENDINGIN DAN KEDALAMAN POTONG PADA PROSES BUBUT BAJA ST60 TERHADAP UMUR PAHAT - Ahmad Khoirul Anwar; Digdo Listyadi; Dwi Djumhariyanto (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2019)
Turning machining process is a warkpiece diameter reduction by using chisel cut to produce the shape of the workpiece on a turning, there are various types of machining turning chisel pieces on the turning chisel types include carbide, CBN, and insert. There are also other types on conventional chisel on a turning process, one of which is a turning type of high speed steel (HSS), the turning is widely used in coventional production processes for other than low cost is also easy to grinding. Parameter in this research is coolant and depth of cut. The coolant used is dromus, ex-oil, ex cooking oil. The depth of cut used is 0,3mm, 0,5mm amd 0,8mm. The highest of tool life in this reserch with dromus as coolant at 0,3mm depth of cut is 83,17 minutes. With ex-oil at 0,3 depth of cut the tool life is 70,79 minutes. And with ex-cooking oil the tool life is 56,77 minutes with 0,3mm depth of cut. While the lowest tool life be obtained with ex-cooking oil coolant at 0,8mm depth of cut is 38,90 minutes. So, the canclusion dromus is a batter then ex-oil and ex-cooking oil. This is caused when the dromus as coolant can mixed with water and become one so can get down temperture of chisel.